STUDI PERAKITAN KELAPA HIBRIDA GSK x DMT BERDASARKAN PENANDA RAPD (RANDOMLY AMPLIFIED POLYMORPHIC DNA) - Runtunuwu, Semuel D.; Novarianto, Hengky; Tampake, Heldering; Lengkong, Edy F. (EUGENIA, 2008)
ABSTRACT   Runtunuwu, S.D. et al. 2008. Assembling Hybrid Coconut of GSK x DMT Based on RAPD (RANDOMLY AMPLIFIED POLYMORPHIC DNA) Marker. Eugenia 14 (1) : 134-152.   The aimed of this research was : 1. assembling hybrid coconut GSK x DMT (Genjah Salak x Dalam Mapanget) that seeds growth was relatifly homogeneous based on RAPD (Randomly Amplified Polymorphic DNA) marker and 2. to found the assembling method of hybrid coconut that will produce massive seeds relatifely short time will homogeneous plant. It was 65 individu trees observe for the average of famale flower per bunch. The result was 25 individu of coconut GSK has the average flower production > 40 per bunch was analyze the homogeneous genetic with the RAPD marker. Based on the analyze RAPD that were 25 individu of GSK coconut trees have the same genetic average 88 % and 14 individu among that was 100 % have same genetic. Further more that 14 individu of GSK was crossing with the 3 individu of DMT that have high yield per year its was DMT 1188, 1172 and 781. Based on the evaluation for the color of buds, high of buds, the steam circle, the petiole color and the germination time of hybrid coconut seeds from the crossing of GSK x DMT 1188 produce more than    70 % seeds that have same genetic, also for crossing of GSK x DMT 1172 have 9 combination and have more than 70 % that same genetic, 10 combination from crossing GSK x DMT 781 have more than 80 % same seeds growth. Therefore, using the RAPD marker were successfully produced 28 crossing of the hybrid coconut GSK x DMT that have relatifly homogeneous seeds growth.   Keywords : assembling, hybrid coconut GSK x DMT, RAPD.